Counseling on Correct Breastfeeding Methods and Lactagogue Plants for Pregnant and Breastfeeding Women in Way Huwi Village, Jati Agung District, South Lampung Regency - Ika Fitria Elmeida; Risneni; Monika Dara Delia Suja (Jurnal Pengabdian Pancasila (JPP), 2023)
This Community Service activity aims to provide education on proper breastfeeding methods and education about plants and foods that can facilitate and increase breast milk production. One of the efforts that can be made to increase the coverage of exclusive breastfeeding is proper breastfeeding and consumption of plants and foods that can facilitate and increase milk production. The activity went well and was carried out on September 2 2022 at the Posyandu Buegenville, Way Huwi Village, which is included in the Working Area of ​​the Karang Anyar Health Center. Participants received counseling on how to breastfeed properly and information about lactagogue plants that can expedite and increase milk production. In addition, participants were given lactagogue plant seeds such as moringa, katuk and legume seeds and planted directly on the land. It is hoped that this activity can be useful and can provide knowledge to pregnant women about how to breastfeed and can increase milk production for nursing mothers by correct breastfeeding and consumption of lactagogue plants.